Diversity of Leguminosae in the Chapada das Mesas National Park, Maranhão, Brazil: new occurrences for Maranhão and the Brazilian Cerrado - Da Silva, Guilherme Sousa; Da Silva Gomes, Gustavo; Dos Santos Gonçalves, Anastácia; Teixeira De Queiroz, Rubens; Mendes Da Conceição, Gonçalo (Phytotaxa, 2022)
The Chapada das Mesas National Park is an important conservation unit in the state of Maranhão, Northeastern Brazil, with a predominance of the Cerrado phytogeographic domain and few floristic studies performed. The study aimed to provide a checklist of the Leguminosae from the Chapada das Mesas National Park through the analysis of samples collected in this study and material previously collected in the park, contributing to the botanical knowledge of the area and the state of Maranhão, in addition to filling data gaps on ecotonal zones in Brazil. Sixty-two genera and 158 species were recorded, corresponding to about 12.4% of the species cited for Cerrado phytogeographic domain and 35.5% of those cited for Maranhão. The subfamily Papilionoideae presented greater richness of genera (37) and species (80). The most representative genera in number of species were Chamaecrista Moench. (12), Mimosa L. (11), and Bauhinia L. (10). Among the recorded species, 27 are endemic to Brazil. With the checklist, 13 new records were cataloged for the state of Maranhão and for Cerrado. The data presented here expand the knowledge of Leguminosae in Maranhão and Cerrado and encourage the conservation of the flora of the Cerrado in Maranhão in view of the strong risk of environmental degradation, with continuous devastation even within protected areas.